Rural poverty and Food insecurity mapping at district level for improved agricultural water management in the Limpopo River Basin - Magombeyi, Manuel Simba; Akpofure, Taigbenu; Barron, Jennie (CGIAR Challenge Program on Water and Food, 2013)
The Challenge Program on Water and Food (CPWF) Phase II for the Limpopo Basin Development Challenge (LBDC) project aims to develop methods, processes, and technologies to help resource- constrained smallholder farmers mitigate poverty and food insecurity through improved agricultural water management (AWM) strategies. The purposes of this paper are to: 1) Identify areas in the Limpopo River Basin with high levels of rural poverty and food insecurity; 2) Identify areas where AWM interventions are taking place; and 3) Check whether current activities of the CPWF in the Limpopo Basin are located in areas of need as per poverty profiles and geographical location of smallholder farms. The generated poverty and food insecurity maps were based on food security surveys and estimates of consumption or income-based welfare outcomes at the district level from 2003–2013. Based on existing district level poverty and other relevant data in the basin, the study shows that the LBDC study sites are located in poor areas in the Limpopo Basin, and poverty reduction efforts should prioritize vulnerable female and child-headed households as they are the most negatively impacted by poverty and food insecurity in the four countries. Hence, with the overall aim of CPWF under LBDC to reduce poverty and food insecurity, and improve livelihoods, poverty indices should rank highly as one of the factors for project site selection. Poverty and food insecurity mapping plays an important role in identifying areas lagging behind in social and economic development, and also in facilitating targeted developmental programs such as education, health, access to credit, agricultural production support and food aid. However, it should be recognized that using district-level information often masks the existence of poverty pockets in otherwise relatively well-off districts, which could lead to poorly targeted AWM schemes. In addition, the poverty index is limited by the subjective nature of community-level and household-level factors that influence it, and this is reflected by the responses from research participants. Whereas a common poverty line for a particular time frame enables poverty comparisons across countries, local level poverty assessments, however, usually require more in-depth and diverse information that can be used in designing cost-effective and efficient anti-poverty programs and livelihoods enhancement opportunities. In order to achieve the research project’s goals of poverty and food insecurity reduction, and livelihood enhancement of smallholder farmers in the Limpopo Basin, it is of greater significance to understand trends in poverty rates rather than 1-year values at CPWF-LBDC study sites. Poverty maps that highlight areas marginalized by resource constraints help in setting priorities for developing technologies and in deploying resources where they are most needed and likely to alleviate poverty and food insecurity. This work provides background information on the Limpopo Basin.